Canonical Doctrinal Foundations of Lay Participation in Positions of Authority in the Church in the Reforming Dynamism of Pope Francis - Jacinto Muñoz, Erika (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2025)
With Pope Francis, the participation of the lay faithful in the life and mission of the Church has regained importance in the overall reform of the Church in its synodal dimension, because their presence and participation are essential, as they cooperate for the good of the whole Church. Hence the proposal for a theoretical foundation of ecclesiological and canonical doctrine that gives strength to the ecclesial reforms promoted by Francis, which allow for a greater presence and participation of the laity in positions of authority, including in the exercise of the power of governance.